Internalization of Religious Character through Qur’an Extracurricular Activities - Pendra, Rangga Septa; Faizin, Faizin; Jamin, Ahmad; Wisnarni, Wisnarni (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2024)
This study examines the internalization of students’ religious character through the LPQ (Al-Qur’an Education Institution) extracurricular program at SMP N 1 Sungai Penuh. The program emphasizes comprehensive planning encompassing clear objectives, structured activity design, management responsibilities, scheduling, and appropriate learning environments to develop students’ competencies in reading, writing, memorizing, and applying the Qur’an. Classes are organized according to students’ proficiency levels, enabling teachers to align instructional complexity with individual learning capacities effectively. The implementation follows a systematic three-stage process: preparation, execution, and closure. Educators employ diverse instructional strategies, including halaqah sessions, memorization exercises, practical worship activities, and interactive educational games, to actively engage students while reinforcing Qur’anic values. Sessions commence with prayers and motivational activities to foster mental and spiritual readiness. Closure activities, encompassing evaluations, question-and-answer sessions, and reflective exercises, strengthen students’ ethical conduct, discipline, and spiritual responsibility. Findings reveal measurable improvements in students’ religious attitudes, Qur’anic reading proficiency, memorization skills, and participation in religious practices. The study demonstrates that structured, well-planned, and consistently executed extracurricular programs are effective in cultivating students’ moral, spiritual, and ethical development, fostering disciplined, responsible, and pious individuals.